Etiudy Agnieszki Osieckiej - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
Agnieszka Osiecka’s Student Films In 1957, the famous young Polish poet and song lyrics writer Agnieszka Osiecka (1936-1998) began studying in the Film School in Łódź. She studied film directing in 1957-1961. After graduating in film arts, she decided not to pursue a professional career in cinema. This analytical essay charts the history of the Film School in Łódź in the 1950s, the student works of Osiecka, and the inspiring confluence of audiovisual culture and film. The essay also explores in detail a wide spectrum of Polish film art of that period, providing original interpretations of eight études made by the young and talented artist during her film directing studies in Łódź.